Comparative Sero-Analysis between Copper Levels and the Risk of Acute Myocardial Infarction in District Nowshera: Copper Levels in Acute Myocardial Infarction Patients - Orakzai, Shabir Ahmed; Khattak, Munaza; Muhammad, Pervez; Khan, Aurangzeb; Baloch, Farhan Abbas; Rasheed, Haroon ur (Pakistan Journal of Health Sciences, 2024)
There is an increasing evidence pointing to a possible correlation between AMI and copper levels. Serum copper levels serve as a valuable biomarker for assessing the body's copper status. Objective: To find the changes in serum copper level in patients with Acute Myocardial Infarction (AMI). Methods: This observational study was conducted in District Headquarter Hospital, Nowshera in duration of two years. A total of 240 patients were recruited in this study. Upon admission, demographic information, medical history, and clinical characteristics were collected. Blood samples were obtained for measurement of serum copper levels using established laboratory methods. All data were analyzed through SPSS version 29.0. Results: Among total, 65% males and 35% females and the prevalence of cardiovascular risk factors was notable, with 70% of patients having hypertension, 40% with diabetes mellitus, 60% with dyslipidemia, and 45% identified as smokers. Baseline serum copper levels averaged 110 ± 5.2 µg/dL, within 24 hours of admission, the peak serum copper level significantly increased to 125 ± 18.6 µg/dL. Subsequently, levels decreased gradually over the following days, with mean values of 120 ± 17.1 µg/dL on Day 2, 115 ± 16.4 µg/dL on Day 3, 112 ± 15.9 µg/dL on Day 4, and returning to baseline levels by Day 5, 110 ± 15.2 µg/dL. Conclusions: Serum copper levels exhibit significant changes during the acute phase of AMI, with a peak observed within 24 hours of admission. While patients with anterior infractions showed higher peak copper levels, no significant associations were found between copper levels and traditional cardiovascular risk factors or inflammatory markers